Dealing with the Dutch disease: Fiscal rules and macro-prudential policies - Javier García-Cicco; Enrique Kawamura (Inter-American Development Bank (IDB), 2015)
This paper evaluates from a welfare perspective three policy alternatives for dealing with Dutch disease problems originating from cyclical movements in commodity prices: fiscal rules for government expenditures, capital controls, and taxes on domestic lending. A DSGE model of a small open economy is developed, with a sectoral decomposition that features three distinctive characteristics: financial frictions, a learning-by-doing externality in the industrial sector, and a fraction of households being non-Ricardian (credit constrained). The model is calibrated using Chilean data. For each policy tool, optimal simple rules are analyzed from a welfare (Ramsey) perspective, describing how different households rank the several policy alternatives, and studying how each of the models features shapes the optimal policy design. A general conclusion of the analysis is that the included Dutch disease inefficiencies are of quantitatively limited relevance in analyzing the desirability of these policies from a welfare perspective.
hdl:11319/7087
Keywords: F41; E61; 330; Dutch Disease; Fiscal procyclicality; Fiscal rules; Capital controls; Macro-prudential policies